2019
DOI: 10.1088/1361-665x/ab1ebf
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric breakdown strength measurements with silicone-based single-layer dielectric elastomer transducers

Abstract: Dielectric elastomer transducers (DETs) consist of an elastic dielectric film sandwiched between compliant electrodes. Applying an electric voltage leads to an electrostatic pressure between the electrodes which causes a deformation of the DET due to the elastic dielectric. The dielectric breakdown field strength of the elastomer restricts the applied voltage. For highly efficient DETs, their dielectric breakdown strength during operation has to be known. In this work, eight different breakdown test scenarios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…, where E b0 = 80 V/μm is the breakdown electric field with no pre-stretch and as reported by the manufacturer (Wacker Chemie AG). Note that the E b0 adopted in this study is relatively conservative as a higher value of E b0 = 90 V/μm was reported in [36].…”
Section: Model Validation 31 Dcdea Fabricationmentioning
confidence: 95%
“…, where E b0 = 80 V/μm is the breakdown electric field with no pre-stretch and as reported by the manufacturer (Wacker Chemie AG). Note that the E b0 adopted in this study is relatively conservative as a higher value of E b0 = 90 V/μm was reported in [36].…”
Section: Model Validation 31 Dcdea Fabricationmentioning
confidence: 95%
“…MR stretch (pure-shear test) 8.2 5.2 5.5 [70] Relative permittivity a) , ε=ε 0 [71,72] www.advancedsciencenews.com www.advintellsyst.com guarantee low material cost but lead to scarce durability in DE applications. Guaranteeing appropriate quality of DE films manufacturing seems key to reach lifetimes consistent with DEGS requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Elastosil silicone holds elastic modulus, dielectric constant and elongation at break similar to those of rubber, and maximum measured BD field of 195 kV mm − 1 . [ 71 ] Based on the product εEBD2, natural rubber appears virtually capable of larger convertible densities than silicone within a same stretch range. However, a systematic characterization of the BD strength at different stretches is currently missing for Elastosil, hence making a reliable comparison not particularly significant.…”
Section: Generalities On Degsmentioning
confidence: 99%
“…The non-dimensional damping coefficient is given as = 0.04 and the pre-stretch ratio is λ P = 1.02. It is noteworthy that, with the material parameters adopted in this work, the nominal electrical breakdown electric field is about 90 MV/m with no pre-stretch [49] , while the applying nominal amplitude adopted in this study is equivalent to about 40 MV/m, which is significantly lower than the critical value.…”
Section: Nonlinear Dynamic Responsesmentioning
confidence: 98%